2013
DOI: 10.1123/rsj.37.2.106
|View full text |Cite
|
Sign up to set email alerts
|

Heterosexism in Campus Recreational Club Sports: An Exploratory Investigation into Attitudes toward Gay Men and Lesbians

Abstract: This study investigated attitudes toward gay men and lesbians among recreational club sport participants, including an investigation of differences in attitudes across sport clubs, team and individual sports, gender, and contact with gay men and lesbians. This study used a modified version of the Attitudes toward Lesbians and Gay Men scale administered online to acquire overall attitudinal scores of participants, as well as two parallel subscale scores. Utilizing MANOVA and ANOVA statistical testing procedures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 27 publications
2
28
0
Order By: Relevance
“…For example, research has shown that LGBTQ sport and recreation clubs create safe spaces for sexual minorities, have positive social psychological benefits, and also challenge the heteronormative assumptions behind mainstream sport and recreation through which heterosexual participants promote a more inclusive masculinity (Jarvis, 2015;Krane, Barber, & McClung, 2002;Ravel & Rail, 2006). Offering a space in which such outcomes can flourish is particularly important in offsetting the negative outcomes from existing stigma and heterosexism found in previous studies of recreation and sport settings (Petty & Trussell, 2018;Anderson, 2017;Anderson & Mowatt, 2013). Universal goals of inclusion create a non-critical normative view that (potentially) benefits segments of the LGBTQ population who can bargain their other privileged identities (Chen, 1999;Duggan, 2002) to the detriment of other segments for whom assimilation is either not possible or not desired (Knee, 2018;Tilsen & Nylund, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, research has shown that LGBTQ sport and recreation clubs create safe spaces for sexual minorities, have positive social psychological benefits, and also challenge the heteronormative assumptions behind mainstream sport and recreation through which heterosexual participants promote a more inclusive masculinity (Jarvis, 2015;Krane, Barber, & McClung, 2002;Ravel & Rail, 2006). Offering a space in which such outcomes can flourish is particularly important in offsetting the negative outcomes from existing stigma and heterosexism found in previous studies of recreation and sport settings (Petty & Trussell, 2018;Anderson, 2017;Anderson & Mowatt, 2013). Universal goals of inclusion create a non-critical normative view that (potentially) benefits segments of the LGBTQ population who can bargain their other privileged identities (Chen, 1999;Duggan, 2002) to the detriment of other segments for whom assimilation is either not possible or not desired (Knee, 2018;Tilsen & Nylund, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…A semi-structured interview guide was developed by the research team and individually tested by each author via four pilot interviews with aquatic professionals meeting the above inclusion criteria. Initial interview questions were developed based on previous literature defining the current state of LGBTQ inclusion in recreation settings (Allison & Hibbler, 2004;Anderson & Mowatt, 2013;Patchett & Foster, 2015;Theriault, 2017), core competencies for recreation and aquatic professionals, and a generally inductive approach which introduced initial opening questions about the existence of policies/programs (see Table 1). It also relied on participant narratives of their experiences, policies, knowledge, understanding and comfort with LGBTQ participants in aquatic settings, which were prodded for following these general questions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participation in previous AfroAIDSinfo CHI studies might have created the perception among participants that their information needs are being met on a continuous basis, which discouraged participation. Then again, it is also well known that online survey response rates are low [ 25 , 26 , 27 ]. While incentives can increase response rates, it was not introduced in this study [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Generally, existing research has mostly focused on hostility or inclusivity toward lesbians and gay men within sports (Morrow & Gill 2003;Piedra et al, 2017), has adapted instruments devised for other purposes , has used single items (Drummond et al, 2015;Gill et al, 2010;, or has assessed the sexual prejudice in sports-related contexts without distinguishing it from general sexual prejudice (Anderson & Mowatt, 2013;Ensign et al, 2011;Forbes et al, 2002;Gill et al, 2006;O'Brien et al, 2013;Oswalt & Vargas 2013;Roper & Halloran, 2007;Sartore & Cunningham, 2009). For this reason, the SPSS scale was specifically designed to explore specific sexual prejudice toward LG athletes and coaches and to distinguish certain kinds of attitudes within sports, such as negative attitudes toward coming-out in sports-related contexts or stereotypes about LG athletes' performance.…”
Section: Convergent and Divergent Validity Of The Spssmentioning
confidence: 99%